The Kumaraswamy compound Rayleigh distribution : properties and estimation - Reyad, Hesham; Othman, Soha A.; Younis, Adil M; Hashish, Ahmed M. (International Journal of Advanced Mathematical Sciences, 2017)
We introduce a new four parameter continuous model, called the Kumaraswamy compound Rayleigh (KwCR) distribution that extends the compound Rayleigh distribution. We study some mathematical properties of this distribution such as; mean, variance, coefficient of variation, quantile function, median, ordinary and incomplete moments, skewness, kurtosis, moment and probability generating functions, reliability analysis, Lorenz, Bonferroni and Zenga curves, RÃ©nyi of entropy, order statistics and record statistics. We consider the methods of moments and maximum likelihood for estimating the model parameters.